AtZAT10/STZ1 improves drought tolerance and increases fiber yield in cotton - Qin, Lixia; He, Hehe; Yang, Liqun; Zhang, Huanyang; Li, Jing; Zhu, Yonghong; Xu, Jianguo; Jiao, Gaili; Xiang, Chengbin; Wang, Chuangyun; Wu, Shenjie (Frontiers in Plant Science, 2024)
Drought poses a significant challenge to global crop productivity, necessitating innovative approaches to bolster plant resilience. Leveraging transgenic technology to bolster drought tolerance in crops emerges as a promising strategy for addressing the demands of a rapidly growing global populace. AtZAT10/STZ1, a C2H2-type zinc finger protein transcription factor has shown to significantly improve Arabidopsis’ tolerance to various abiotic stresses. In this study, we reports that AtSTZ1 confers notable drought resistance in upland cotton (Gossypium hirsutum), amplifying cotton fiber yield under varying conditions, including irrigated and water-limited environments, in field trials. Notably, AtSTZ1-overexpressing transgenic cotton showcases enhanced drought resilience across critical growth stages, including seed germination, seedling establishment, and reproductive phases. Morphological analysis reveals an expanded root system characterized by an elongated taproot system, increased lateral roots, augmented root biomass, and enlarged cell dimensions from transgenic cotton plants. Additionally, higher contents of proline, chlorophyll, soluble sugars, and enhanced ROS-scavenging enzyme activities are observed in leaves of transgenic plants subjected to drought, underscoring improved physiological adaptations. Furthermore, transgenic lines exhibit heightened photosynthetic rate, increased water use efficiency, and larger stomatal and epidermal cell sizes, coupled with a decline in leaf stomatal conductance and density, as well as diminished transpiration rates compared to the wild type counterparts. Transcriptome profiling unveils 106 differentially expressed genes in transgenic cotton leaves post-drought treatment, including protein kinases, transcription factors, aquaporins, and heat shock proteins, indicative of an orchestrated stress response. Collectively, these findings underscore the capacity of AtSTZ1 to augment the expression of abiotic stress-related genes in cotton following drought conditions, thus presenting a compelling candidate for genetic manipulation aimed at enhancing crop resilience.